Protecting health or protecting imports? Evidence from EU non-tariff barriers - Fatima Olanike Kareem; Immaculada Martinez-Zarzoso; Bernhard Brümmer (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
Non-tariff measures such as food safety standards are used to achieve the non-trade objective of protecting consumers' health and safety. However, they can also be used as a trade protection tool to drive a price wedge between domestic and foreign producers. This study investigates the protectionist intent of EU food safety standards using a sample of EU food imported from African countries with a specific focus on tomatoes and citrus fruits. We formalize what protectionism is by comparing EU standards to the internationally scientific referenced benchmarks regulated jointly by both the Food and Agricultural Organization and the World Health Organization. Our results show that the EU tomato sector is less dependent on imports and is overprotected by more stringent standards relative to the international benchmarks. Conversely, we find that the EU orange and lime and lemon sectors are heavily import dependent and are under-protected relative to the international standards. These results largely support the hypothesis that heavily import dependent sectors are less protected.
Keywords: F13; F14; L15; P16; Q17; Q18; 330; Trade Protectionism; Non-tariff barriers; Food Safety Standards; Food exports